DIKLAT BASIC SAFETY TRAINING (BST) KAPAL LAYAR MOTOR SUNGAI LIAT KEPULAUAN BANGKA - Santiko, Tony; Tazani, Afdolludin Afta (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2021)
The Government of the Republic of Indonesia through the Ministry of Transportation commissioned the Semarang Polytechnic of Shipping Science to conduct basic safety training (BST) of motor yachts to certify the crew of tourist boats and fishermen in Sungai Liat Bangka Regency. This activity is based on a letter of request from KSOP Sungai Liat to the Semarang Polytechnic of Shipping Sciences which aims to improve the competence of the Crew related to shipping safety and marine environmental pollution. Instructors and Lecturers of Semarang Polytechnic of Shipping Sciences as Resource Persons conduct education, training and counseling to the crew of tourist boats and Fishermen of Sungai Liat in order to implement safety and security in carrying out their duties and also support the protection of the marine environment for the common.